Effect of 4 weeks of rock climbing with and without blood flow restriction, on Serum Levels of CRP, LDH and CK in elite rock climbers - fateme halalkhor; Mansour Aghaei; Jawad Vakili (Shahid Beheshti University, 2021)
purpose: Exercise training with blood flow restrictionare associated with immunological changes as well as changes in the indices of inflammation and muscle damage. Therefore, the aim of this study was conducted to identify the effect of 4 weeks rock climbing with and without blood flow restriction on response of the LDH, CK and CRP in elite rock climbers. Methods:12 elite male and 12 female rock climbers with at least 4 years rock climbing experience and age range of 23.54±2.32 to 27.18±3.18 years and a fat percentage of 8.22±1.12 to 14.19±1.18 percent were selected purposefully among elite climbers and randomly assigned to one of two groups The exercises were limited by blood flow and exercise without limitation of blood flow. The exercise protocol was performed for 4 weeks (three sessions per week and each session was 90 minutes, severity of each session was 60 to 80% of climbing grades). Blood samples were taken in two stages (pre and post test) in sitting and resting conditions to determine the amount of lactate dehydrogenase, creatine kinase, blood lactate and C-reactive protein. To analyze the data, an independent test was used to compare the meanings and Kolmogorov-Smirnov test for homogeneity of the two groups at a significant level of α ≤0.05. Results: The results showed that the index of muscle damage of LDH, CK and inflammatory CRP index did not show a significant difference in response to climbing exercises with and without blood flow restriction between the two groups (P <0.05). Conclusion: According to the results of this study, rock climbing training with or without blood flow restriction, do not increase inflammatory and muscular damage, and this method of training is likely to be safe for climbers due to the mechanical and metabolic pressure of exercise activity.